Exploring Active Learning in Papua: A Corpus and Conversation Analysis of EFL Classroom Discourse - Mardiana, Rizdika; Fatkhiyati, Nurrahma Restia; Mukhamdanah, Mukhamdanah; Lubis, Bambang Nur Alamsyah; Permana, Sudarya (Journal of Language and Literature Studies, 2026)
This study investigates how active learning is conducted in EFL classroom discourse in Papua by combining Corpus Linguistics and Conversation Analysis (CA) framework. It specifically examines how lexical patterns and interactional organization jointly shape students’ communicative development from five datasets. A mini spoken corpus was constructed from the video-recorded lessons and analyzed for lexical frequency, collocations, and formulaic language. In terms of CA, turn-taking, repair practices, and teacher scaffolding of the classroom conversations were identified. The findings reveal systematic variation across task types. Genre-focused lessons are dominated by metalanguage and definitional bundles, reinforcing classification routines within teacher-controlled IRF sequences. While performance-based and narrative tasks generate longer student turns supported by formulaic expressions and temporal markers. This facilitates discourse expansion and storytelling competence. Grammar-driven descriptive tasks prioritize structural templates, promoting accuracy but limiting lexical diversity. Across datasets, formulaic language functions as an interactional scaffold that enables participation despite limited grammatical complexity. However, repair practices operate as learning opportunities. The study demonstrates that communicative growth in active EFL classrooms is strongly shaped by task design and pedagogical orientation. Narrative and pragmatic performance tasks foster greater interactional competence than taxonomy-driven instruction. As for the methodology, the combination of corpus linguistics and CA framework provides a comprehensive account of how lexical recycling, scaffolding, and sequential organization provide learning opportunities in real-time classroom interaction. The findings offer pedagogical implications for designing tasks that expand learner autonomy and promote sustained student talk in multilingual and under-researched contexts such as Papua.